Artificial Intelligence Applications in Healthcare Diagnosis and Treatment in the Era of Big Data - Kai, Qi (Pacific International Journal, 2025)
The integration of artificial intelligence (AI) into healthcare is transforming medical practices, particularly in diagnosis, treatment, and drug discovery. This study explores the applications of AI in healthcare through the case studies of Tempus Labs, PathAI, and Insilico Medicine, focusing on their use of big data and machine learning algorithms to enhance precision medicine, optimize drug development, and improve patient outcomes. Tempus Labs leverages AI for personalized cancer treatment by analyzing genomic and clinical data, while PathAI applies deep learning algorithms for accurate medical image analysis, and Insilico Medicine utilizes AI in drug discovery. The study highlights the significant role of big data in facilitating AI-driven advancements and discusses how these technologies improve efficiency, reduce healthcare costs, and personalize treatment. However, challenges such as data privacy, integration with existing healthcare systems, and ethical concerns are also addressed. As AI continues to evolve, its potential for revolutionizing healthcare practices is immense, ushering in an era of personalized, data-driven, and cost-effective medical care.